2003
DOI: 10.1103/physrevlett.91.227403
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Optical Phonons and Parametrically Coupled Magnons Induced by Femtosecond Laser Excitation of the Gd(0001) Surface

Abstract: Coherent spin dynamics in the THz domain coupled to a coherent phonon is observed in the time-resolved second harmonic response of the Gd(0001) ferromagnetic metal surface. An LO phonon of 2.9 THz is excited by a transient charge displacement at the surface caused by resonant absorption of a fs laser pulse in the exchange-split surface state. This lattice vibration modulates the interlayer distance inducing a coherent variation of the exchange interaction between spins in adjacent layers. The resulting magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
96
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 25 publications
6
96
0
Order By: Relevance
“…[13] They focused their attention into the generation mechanism of the coherent optical phonon and coupled coherent magnon. The surface coherent optical phonon was excited by a transient charge separation at the surface, which is similar proposal to the displacive excitation mechanism (DECP).…”
Section: Introductionmentioning
confidence: 99%
“…[13] They focused their attention into the generation mechanism of the coherent optical phonon and coupled coherent magnon. The surface coherent optical phonon was excited by a transient charge separation at the surface, which is similar proposal to the displacive excitation mechanism (DECP).…”
Section: Introductionmentioning
confidence: 99%
“…To reveal the origin of this dynamics, we note that the pump-induced oscillations are usually related to the excitation of quasiparticles [42][43][44][45][46], for instance, magnons or phonons. However, our experiments have shown that neither the phase of the oscillations changes upon switching the magnetic field, nor their frequency shifts when the magnetic field strength is changed (see Sec.…”
Section: Long Time Rangementioning
confidence: 99%
“…12,13,17,21,25 The observation of coherent longitudinal optical ͑LO͒ phonons in Gd was reported in Refs. 12, 13, 21, and 25.…”
mentioning
confidence: 87%